ТАБАҚАЛАШТИРИШ АСОСИДА ЖИСМОНИЙ ТАРБИЯ ДАРСЛАРИНИ ТАШКИЛ ЭТИШ МЕХАНИЗМЛАРИ - Зайниддинов, Т.Б. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of pedagogical, physiological and physiological aspects of learners of primery schools by using the whole approach.
Keywords: physical education; elementary school; differentiation; pedagogy; psychology; individualism; action; normalization